Pentingnya soft skill dalam meningkatkan kesiapan mahasiswa - ramadhan, gilang (Maliki Interdisciplinary Journal, 2025)
In facing the challenges of an increasingly competitive workplace in the era of globalization, students are not only required to possess academic abilities (hard skills), but also non-technical skills or soft skills that include communication, leadership, cooperation, and adaptability. This study aims to explain the important role of soft skills in improving students’ readiness to enter the workforce and their development strategies in higher education. The results of the study indicate that mastery of soft skills has a significant influence on students’ readiness to face the professional world. Soft skills development can be done through active involvement in student organizations, seminars, training, social projects, and the application of innovative learning methods such as blended learning that combines theory and practice. In conclusion, soft skills are an essential factor that supports career success and the formation of student character. Higher education institutions need to design integrated and sustainable programs so that students are ready to compete academically, socially, and emotionally in the workplace.